Proceedings of the 11th ACM Symposium on Eye Tracking Research &Amp; Applications 2019
DOI: 10.1145/3317959.3321490
|View full text |Cite
|
Sign up to set email alerts
|

Attentional orienting in virtual reality using endogenous and exogenous cues in auditory and visual modalities

Abstract: The virtual reality (VR) has nowadays numerous applications in training, education, and rehabilitation. To efficiently present the immersive 3D stimuli, we need to understand how spatial attention is oriented in VR. The efficiency of different cues can be compared using the Posner paradigm. In this study, we designed an ecological environment where participants were presented with a modified version of the Posner cueing paradigm. Twenty subjects equipped with an eye-tracking system and VR HMD performed a sandw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Human attention is limited [2,27], so the use of alerts to notify people needs to be carefully designed to both alert and direct people's attention to situations or objects present in both the interface and/or the outside world [39]. Notifications are commonly sub-divided into two categories: push and pull [5].…”
Section: Context-aware Notifications In Mixed Realitymentioning
confidence: 99%
“…Human attention is limited [2,27], so the use of alerts to notify people needs to be carefully designed to both alert and direct people's attention to situations or objects present in both the interface and/or the outside world [39]. Notifications are commonly sub-divided into two categories: push and pull [5].…”
Section: Context-aware Notifications In Mixed Realitymentioning
confidence: 99%
“…Furthermore, we developed and tested the method only for standard keyboard input and did not include support for the HTC Vive's motion controllers. Motions controllers are increasingly used to investigate naturalistic behavior, as they allow to track the hand movements of the participant [e.g., 52,53]. Future research needs to assess timing errors related to motion controllers.…”
Section: Discussionmentioning
confidence: 99%
“…The results [Soret et al 2019] revealed a main validity effect (faster RT in the valid condition compared to invalid condition) showing that Posner's paradigm is transferable in VR. We also observed that while flash and voice instruction seems to effectively direct a person's attention to the desired region of space, the directional arrow and spatialized sound seemed to have more difficulties directing attention to a specific location and instead direct attention to a particular hemifield (left or right).…”
Section: Preliminary Studymentioning
confidence: 99%
“…We performed the preliminary study [Soret et al 2019] where we used a modified version of Posner's paradigm with a head-mounted display considering the visual and auditory modalities. We tested the transferability of Posner paradigm in VR.…”
Section: Preliminary Studymentioning
confidence: 99%